'˜PAP SMEAR' FOR SCREENING OF PRECANCEROUS CONDITIONS OF CERVIX - Noreen, Rubia; Qudussi, Huma (Journal of Ayub Medical College Abbottabad, 2011)
Background: Cervical intra-epithelial neoplasia (CIN) and cervical cancer remain important health problems for women worldwide. It is largely a preventable disease that is characterised by a long lead time. The objective of this study was to determine the frequency of precancerous conditions of cervix (CIN I-III) in women with chronic vaginal discharge by Pap smear screening. Methods: The study was conducted at the outpatient department of Obstetric and Gynaecology, Nishtar Hospital Multan, and Multan Institute of Nuclear Medicine & Radiotherapy (MINAR) from February 2009 to February 2010. Two hundred and eighty patients with complaint of chronic vaginal discharge were selected. Their detailed history was documented on a Proforma, Pap smear taken at MINAR, and samples sent to pathology department of Nishtar Hospital Multan for cytological examination. All mild dyskaryosis or CIN I cases were advised follow-up with repeat Pap smear in 6-12 months and those with moderate to severe neoplasia (CIN II-III) were further investigated by cervical biopsy and managed accordingly. Results: Of the total, 100 patients were between 25-30 years of age, and 180 between 31-35 years of age. Mean age of patients was 31.6 years, mean age at marriage 21.7 years, and mean parity was 3.6. Most of the patients (67.9%) belonged to low socioeconomic status. The cytological examination of the smears showed no changes (normal) in 100 (35.7%) cases, while 156 (55.7%) cases showed inflammatory changes, 10 (3.6%) showed dysplastic changes, of whom 8 cases had CIN-I (2.8%) and one case was of CIN-II (0.4%). One was having CIN-III/severe dysplasia (0.4%). Inadequate sample was reported in 14 (5%) cases. Conclusion: Pap smear should be used as a routine test for all sexually active, young females presented to the gynaecology outpatient department, for early detection of cervical pre cancer (CIN) as it is not uncommon in our set up. Keywords: Pap smear, Cervical Intraepithelial Neoplasia, CIN, cervical, Screening Program